An Analysis of Hospitality Students’ Speaking Difficulties in the Hotel Front Office at SMKN 1 Sintuk Toboh Gadang - Iva Octi R. Ramli; Aryuliva Adnan (Universitas Negeri Padang, 2020)
This study analyzes hospitality students’ speaking difficulties in hotel front office and the causes of the speaking difficulties in grade eleven at SMKN 1 Sintuk Toboh Gadang. The purpose of this research are to find out hospitality students’ speaking difficulties in front office grade eleven at SMKN 1 Sintuk Toboh Gadang and the causes of hospitality students’ difficulties in speaking. This research used descriptive qualitative method in order to analyze hospitality students speaking difficulties and the causes in hotel front office. The instrumentation of this research is questionnaire sheets. Based on the findings of the study it was found that hospitality students ‘speaking difficulties namely (1) lack of vocabulary 50.00%, 15 students, (2) difficult to understand 47.58%, 15 students, (3) poor in grammar 54.03%, 17 students, (4) poor in pronunciation 51.61%, 16 students, and (5) fluency 65.32%, 20 students. The researcher also found the causes of hospitality students’ speaking difficulties: (1) lack of confident 40.32%, 12 students, (2) anxiety 62.90%, 19 students, (3) inhibition 45.15%, 14 students, (4) nothing to say 46.23%, 14 students, (5) mother tongue use 37.63%, 12 students. The results of this research indicate that hospitality students grade eleven faced difficulties in speaking at hotel front office.